The Public Health Nurse Workforce in U.S. State and Local Health Departments, 2012. (January 2016) - Beck, Angela J.; Boulton, Matthew L.
Objective: Public health nurses (PHNs) represent the single largest group of public health practitioners working in U.S. state and local health departments. Despite the important role of PHNs in the delivery and administration of public health services, little research has been conducted on this group and relatively little is known about PHN education, training, and retirement intentions. We describe the findings of a nationally representative survey of PHNs working in state and local health departments by characterizing their educational background and plans for retirement. Methods: An advisory committee convened by the University of Michigan Center of Excellence in Public Health Workforce Studies developed the Public Health Nurse Workforce Survey and disseminated it in 2012 to 50 U.S. state and 328 local health departments. Results: The 377 responding state and local health departments reported an estimated 34, 521 full-time equivalent registered nurses in their employ, with PHNs or community health nurses as the largest group of workers (63%). Nearly 20% of state health department PHNs and 31% of local health department PHNs were educated at the diploma or associate's degree level. Approximately one-quarter of PHNs were determined to be eligible for retirement by 2016. Professional development and promotion opportunities, competitive benefits and salary, and hiring procedures were among the recruitment and retention issues reported by health departments. Conclusion: PHNs were reported to have highly variable occupational classifications and educational backgrounds in health departments. Additional training opportunities are needed for PHNs with diploma and associate's degrees. A shortage of PHNs is possible due to retirement eligibility and administrative barriers to recruitment and retention.